Personal Branding Politik Thoriqul Haq Melalui Facebook - Rurut Wahyu Trisnanto; Tony Sukasah; Yenny Yenny (Communication, 2020)
The emergence of social media makes many variations in political communication. The rise in the use of Facebook sosial networks among modern society especially among young people makes Facebook as popular sosial network today. Facebook's popularity cannot be separated from its use as a sosial network that uses photos, videos as a communication tool, thus allowing users to create their personal branding to the publik through Facebook social media. Facebook also allows users to do personal branding politics through uploads and platforms that they upload. One of the politicians who use Facebook as a personal branding media is Thoriqul Haq. Through informative and educative and persuasive approaches and methods. To build the expected political image, Thoriqul Haq has delivered repeated messages on social media with an informative and educative, and persuasive approach. Broadly speaking, the political communication strategy carried out is optimal, especially in building political image as a new player in the political arena.